Sonochemically tailored Copper Oxide as nanofiller in terpolymer composite gel electrolytes for dye-sensitized solar cells - Farhana, N.K. (Elsevier, 2024)
This article describes the impact of several weight percentages of copper oxide (CuO) as a nanofiller on the structure, morphology, and electrochemical performance of dye-sensitized solar cells (DSSC). CuO-350 was synthesized using a sonochemical method following by calcination at 350 celcius and was incorporated into the polymer-salt system to develop a polymer composite gel electrolyte (PCGE). The improvement in the amorphous phase and complexation between the constituents were proven via X-ray diffraction, and Fourier transform infrared. However, the thermal stability declines with the addition of CuO-350 nanofillers. It was found that TCuO350-5 exhibited the highest ionic conductivity and apparent diffusion coefficient of triiodide of (3.49 +/- 0.01) x 10- 3 S cm- 1 and 1.48 x 10- 5 cm2 s - 1 , respectively. The best-performing sample among PCGE is found to be TCuO350-5, containing 5 wt% of CuO-350 with an efficiency of 7.69% with JSC of 23.47 mA cm- 2 , VOC of 0.62 V, and fill factor of 52.9%. In addition, it also has the highest charge collection efficiency (87.31%) and longest electron lifetime (1.446 s). TCuO350-5 has achieved the stability of the device with efficiency retained 92% at room temperature and retains 80% efficiency even at 80 celcius.